Relationship Between Screening-Detected Atrial Fibrillation and Blood Pressure Levels in Elderly Hypertensive Patients: The OMRON Heart Study - Senoo, Keitaro; Nakata, Mitsuko; Yukawa, Arito; Kawai, Kohei; Munakata, Jun; Makino, Masahiro; Tomura, Nobunari; Iwakoshi, Hibiki; Nishimura, Tetsuro; Shimoo, Satoshi; Shiraishi, Hirokazu; Teramukai, Satoshi; Matoba, Satoaki (Thrombosis and Haemostasis, 2024)
Hypertension is a well-known risk factor for atrial fibrillation (AF) and strokes, but studies assessing screening-detected AF in hypertensive populations and its relationship to the blood pressure (BP) are scarce.We prospectively recruited hypertensive patients (aged ≥60 years) from all over Japan in a decentralized clinical trial. Participants were asked to measure their electrocardiogram (ECG) and BP at home for 3 months with a BP monitor equipped with ECG.Between April 2022 and July 2023, 4,078 hypertensive patients from across the country participated in this study. The mean age was 66.3 ± 5.5 years, and the male proportion was 80.3%. After excluding those with no measurement data (n = 258), AF detection was 5.8% (n = 220/3,820), and the time to AF detection was 3 to 109 days (median 28 days). The mean BP at baseline was 133 ± 14/85 ± 9 mmHg in the morning and 125 ± 14/79 ± 9 mmHg in the evening. AF detection did not significantly differ between the baseline BP categories (log rank test, p = 0.54), with hazard ratios (95% confidence interval) of 0.83 (0.57–1.19), 0.79 (0.55–1.14), and 0.99 (0.59–1.68) for systolic BP (SBP) 135 to 144 and/or diastolic BP (DBP) 85 to 89, SBP 145 to 159 and/or DBP 90 to 99, and SBP ≥ 160 and/or DBP ≥ 100, respectively (SBP ≤ 134 and DBP ≤ 84 as a reference). The results did not change when taking into account the impact of the measurement rates and antihypertensive drugs on AF detection during the observation period.Detection of undiagnosed AF was 5.8% in elderly hypertensives, with no significant differences between the baseline BP categories and no effect of the measurement rate or antihypertensive drugs.
Keywords: screening; atrial fibrillation; hypertension; decentralized clinical trial